The bronze key - Black, Holly; Clare, Cassandra (Black, Holly. Magisterium, 2016)
Things have been better for Callum Hunt since the evil Constantine Madden was "officially" destroyed, even his relations with his father have improved, so he is happy to get back to the Magisterium for his Bronze Year to continue his magical studies--but when one of the students is murdered, Call and his friends, Tamara and Aaron, must track down the killer, without revealing the fact that Call is Madden reborn.